2018
DOI: 10.1371/journal.pone.0192532
|View full text |Cite
|
Sign up to set email alerts
|

Differences in neural responses to ipsilateral stimuli in wide-view fields between face- and house-selective areas

Abstract: Category-selective brain areas exhibit varying levels of neural activity to ipsilaterally presented stimuli. However, in face- and house-selective areas, the neural responses evoked by ipsilateral stimuli in the peripheral visual field remain unclear. In this study, we displayed face and house images using a wide-view visual presentation system while performing functional magnetic resonance imaging (fMRI). The face-selective areas (fusiform face area (FFA) and occipital face area (OFA)) exhibited intense neura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
(94 reference statements)
0
2
0
Order By: Relevance
“…Although visual impairment in general is associated with reduced socialization [18], patients with central visual loss and impaired face recognition had self-reported difficulty not only in recognizing others, but consequent feelings of guilt, failure, and ultimately social avoidance [25]. Visual association areas in the ventral occipital temporal cortex (VOTC – the FFA and OFA) specialize in face recognition and processing [54] and show increases in activity on fMRI when a facial image is presented in the ipsilateral peripheral VF [55]. Thus, peripheral field involvement in face perception may be more important than previously believed, as its role in face recognition and characterization is inadequately understood.…”
Section: Face Recognition and Peripheral Field Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…Although visual impairment in general is associated with reduced socialization [18], patients with central visual loss and impaired face recognition had self-reported difficulty not only in recognizing others, but consequent feelings of guilt, failure, and ultimately social avoidance [25]. Visual association areas in the ventral occipital temporal cortex (VOTC – the FFA and OFA) specialize in face recognition and processing [54] and show increases in activity on fMRI when a facial image is presented in the ipsilateral peripheral VF [55]. Thus, peripheral field involvement in face perception may be more important than previously believed, as its role in face recognition and characterization is inadequately understood.…”
Section: Face Recognition and Peripheral Field Lossmentioning
confidence: 99%
“…Low spatial frequency (LSF) processing of broad information [68] is carried by magnocellular pathways, corresponding to the peripheral VF [69], while high spatial frequency (HSF) input of the fine details of a scene [68] is carried by the parvocellular pathways from the central VF [69]. Neuroimaging studies have shown that peripheral vision is more important than central vision for categorization of different natural scenes [70,71], with scene categorization tasks shown in the periphery resulting in significant activation of the PPA and transverse occipital sulcus (TOS) in a retinotopic manner [55].…”
Section: Scene Recognition and Scene Navigationmentioning
confidence: 99%